Reproduction, production and draftability performance of Kathani cattle under rural management conditions - RL Bhagat; PK Singh; Marimuthu Swaminathan; NL Phadke (Journal of Livestock Biodiversity, 2025)
Data on 6649 Kathani animals from 118 randomly selected villages from Chandrapur, Gadchiroli and Gondia districts of Vidarbha region in Eastern Maharashtra state were used for present study. Information on reproduction and production traits as well as draft-ability of bullocks was collected from the farmers through breed characterization project. For assessing milk production potential of cows, milk was recorded once in a month. Average age at first mating, age at first calving and average calving interval was 42.84±0.05 months, 54.86±0.05 months and 486.85±0.51 days, respectively. Average number of services per conception was 1.48±0.01. Milk production was 0.55±0.01 kg per day with average fat percentage as 4.4 for an average lactation length 237.76±1.82 days. For ploughing of one-acre of land, an average time 8.62±0.05 hours were required and traveled a distance up to 9.32±0.03 km in a day with average 610.64±5.18 kg load.